THE EFFECT OF DICTATION AS A TECHNIQUE ON THE STUDENTS’ LISTENING COMPREHENSION ABILITY TO THE FIRST GRADERS OF SMP HKBP PADANG BULAN MEDAN - Lidya Agustina Tambunan; Lastri Wahyuni Manurung; Nurhayati Sitorus (Sean Institute, 2023)
Dictation technique is a practice that improves pupils' phonetic knowledge, listening comprehension, and writing abilities. Dictation technique was used to improve students' listening comprehension ability. The objective of this study was to find out whether the dictation technique have effect the listening comprehension ability of first graders of SMP HKBP Padang Bulan Medan. A quantitative experimental research design was used in this study. The population of this study were first graders of SMP HKBP Padang Bulan Medan, totaling 30 students, with a sample of 15 students for each class. Students were divided into two groups, namely the experimental group and the control group. The experimental group was taught using dictation technique, while the control group was taught using conventional methods. The instrument used to collect data was a fill in the blank test which was then divided into pre-test and post-test. Data were analyzed using the t-test formula. The results of the analysis show that t-count is greater than t-table (3.02 > 1,69) at a significance level of 0.05 with degrees of freedom (df) 28, meaning that there is a significant influence of the use of dictation technique on students' listening comprehension ability achievement.